Numerical study on the aerothermodynamics of different heatshield configurations for Mars entry capsules. (April 2019) - Zhong, Kang; Yan, Chao; Chen, Shu-sheng; Wang, Xiao-yong; Ju, Sheng-jun
Abstract: Aeroheating predictions play an important role in the heatshield design of Mars entry capsule. This paper numerically investigates the effects of sphere-cone angle on the aerothermodynamic performances of heatshield configurations. Three-dimensional Navier-Stokes equations with chemical non-equilibrium models are employed to simulate the flowfield around the capsule. The laminar and turbulent heating rates of different heatshield configurations are compared and analyzed in detail. A novel correlation for turbulent heating augmentation in terms of laminar momentum thickness Reynolds number is developed to provide a guidance for engineering design and application. The proposed correlation can be more accurate and applicable due to its consideration of the sphere-cone angle effects. Finally, the laminar and turbulent maximum heat flux and total heat load along the flight trajectory are investigated for all the configurations. The numerical study is expected to illustrate the aeroheating characteristics of different heatshield configurations and provide an insight into the rational configuration design for future Mars entry capsules. Highlights: Flow over heatshields with 60°, 70° and 80° sphere-cone angles is investigated. Laminar and turbulent heat flux are simulated and compared in detail. A novel correlation for turbulent heating augmentation in terms of Re θ is developed. Maximum heat flux and total heat load along the flight trajectory are investigated.